2020
DOI: 10.1186/s12917-020-02300-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and PK/PD cutoff values determination and PK/PD-based dose assessment of gamithromycin against Haemophilus parasuis in piglets

Abstract: Background: Gamithromycin is a macrolide approved for the treatment of bovine and swine respiratory diseases. Our study aims to establish the clinical breakpoint and optimum dose regimen for gamithromycin against Haemophilus parasuis in piglets. Results: Gamithromycin was well absorbed and fully bioavailable (87.2-101%) after intramuscular and subcutaneous administrations. The MICs of gamithromycin for 192 clinical H. parasuis isolates ranged from 0.008 to 128 mg/L and the epidemiological cutoff (ECOFF) was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…From the manuscript, the ECOFF, CO PD and CO CL were determined as 1 μg/mL, 0.06 μg/mL and 0.5 μg/mL, respectively. Compared with CO PD and ECOFF, CO PD is less than ECOFF which indicates the recommended dose regimen is a little bit too low to treat the wild-type population infected by S. suis [ 22 ]. From the clinical experiment, for the pathogens associated with high MIC values, the cure rate is less than 67% at a dose of 2 mg/kg, indicating the dose of cefquinome against S. suis needs to be optimized.…”
Section: Discussionmentioning
confidence: 99%
“…From the manuscript, the ECOFF, CO PD and CO CL were determined as 1 μg/mL, 0.06 μg/mL and 0.5 μg/mL, respectively. Compared with CO PD and ECOFF, CO PD is less than ECOFF which indicates the recommended dose regimen is a little bit too low to treat the wild-type population infected by S. suis [ 22 ]. From the clinical experiment, for the pathogens associated with high MIC values, the cure rate is less than 67% at a dose of 2 mg/kg, indicating the dose of cefquinome against S. suis needs to be optimized.…”
Section: Discussionmentioning
confidence: 99%
“…However, for newer macrolides such as azithromycin and clarithromycin, the plasma AUC/MIC ratio seems to strongly correlated with successful results (Lees, Concordet, Aliabadi, & Toutain, 2006). In addition, recent studies have demonstrated that the use of AUC/MIC as a PK/PD predictor of efficacy is feasible for previously approved veterinary macrolides such as tulathromycin and gamithromycin (Toutain et al, 2017;Zhou et al, 2020). At present, the minimum inhibitory concentration (MIC) of TD against P. multocida isolated from rabbits has not been determined.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
“…The model can establish the relationship between drug concentration, antimicrobial effect, and time. Based on the scientific calculation, the model can provide the optimal dose regimen and dose interval [ 6 ]. Certain PK parameters (i.e., AUC and C max ) and PD parameters (i.e., minimal inhibitory concentration (MIC) and time-kill curve) are commonly considered to integrate the PK-PD model.…”
Section: Introductionmentioning
confidence: 99%